Metamorfose da alma: visões do processo de envelhecimento homossexual masculino - Moreira, Adailson da Silva (2015)
Aging is a phase of life marked by complexity and heterogeneity, there are several ways of being old and live the oldness. In addition, the increasing technological development has provided live longer and better, which implies the possibility of maintaining youthfulness in all areas of life, and in particular, the availability to the affection and sexuality until very advanced ages. Within the male elderly population we can find a considerable portion of individuals who are homosexual, although they do not appear in researches because the sexual orientation is not always taken into consideration in this type of survey. However, with the advancement of acceptance of human sexual diversity, different individuals of different orientations and ages begin to appear in their singularities and specificities. In order to describe and understand the issues and conflicts involved in the male homosexual aging process, we conducted a qualitative study, with 12 participants, at 50 years old or more, to identify how male homosexual experience, perceive and elaborate changes from the aging and the strategies used to deal with this process, building an analysis of their experiences in the light of Analytical Psychology and using the Content Analysis method proposed by Bardin to proceed the analysis of the verbal content. After identification and preliminary grouping, it was possible to identify three major categories to which pointed the research resulting material: life and family stories, sexuality and affective and work relationships and perceptions of aging. The survey results suggest that the male homosexuals who get old had to learn to integrate aspects of their sexuality and affection to consciousness, which means learning to live with both their guidance and advanced age and also dealing with the limitations and obstacles naturally arising in the process to achieve a healthier oldness. Those who thus have yet to experience difficulties and limitations, not reaching satisfactory level of quality of life. The survey results also suggest that the contact with aging provides, on the one hand, the consciousness of positive aspects, as a greater maturity towards himself and life, a better capacity for decision and coping, feeling attractive and happiness. And also considered negative aspects such as disease and signs of age, difficulty with new technologies, lack of affection, nostalgia, loneliness, regrets and fears